Corrosion Inhibition of Mild Steel by Curcuma Extract in Petroleum Refinery Wastewater - S. Yaroa, Aprael; F. Talib, Kabas (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
The inhibitor property of curcuma longa L. extract in different concentrations of simulated refinery wastewater (0.05% - 2% wt) and at various temperatures (30, 35 and 40 ˚C) was investigated using weight loss method. The results showed that the presence of about 1.2 % (v/v) of curcuma extract gave about 84% inhibition indicating its effectiveness on mild steel corrosion in simulated refinery wastewater, besides the adsorption process on the mild steal surface obeyed the Langmuir adsorption isotherm.